Study of Coil Heat Exchanger of Mechatronic Sample Conditioning System - Gimadiev, A.G.; Utkin, A.V. (Procedia engineering, 2017)
The heat exchanger is the main part of mechatronic sample conditioning system. Static and dynamic characteristics of heat exchanger influence on the accuracy of sample temperature maintaining. Adjustable parameter of the heat exchanger is the final sample temperature; the control factor is cooling water flow rate. The inlet sample temperature, the inlet cooling water temperature and the sample flow rate can be attributed to disturbing factors. To ensure the efficient operation of sampling system is necessary to know of heat exchanger characteristics when the control and disturbing factor are present. In present work, secondary countercurrent coil heat exchanger with core tube is studied. On the basis of 30 experiments semi-empirical correlation for prediction of overall heat transfer coefficient is proposed. Temperature transient response is investigated theoretically and experimentally when inlet sample temperature is subjected to sudden change. The dynamic behavior is approximated by aperiodic link with time delay link. The obtained for heat exchanger dynamic dependences can be used in the design of mehatronic sample conditioning system, operating at steady and transient state, in the choice of the law of the controlling sample temperature and the algorithm of diagnosing deposits on the surface of the coil.